Supplementation of swine diets with fat - Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1985)
After several years of intensive research) the addition of fat to swine diets continues to generate spirited discussion. The use of cereal grain-soybean meal diets in the swine industry is popular because of the plentiful supply and current low price of cereal grains. Fat is an excellent energy source for all classes of swine, with a value approximately 2.25 times that of carbohydrates.; Swine Day, Manhattan, KS, November 21, 1985
Keywords: Swine day; 1985; Kansas Agricultural Experiment Station contribution; no. 86-145-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 486; Swine; Supplementation; Fat